Main sites of helminth infection reported in marsupials of the genus Didelphis sp. and the perspective of the parasite-host relationship - Araújo Ferreira, Lucas (2025)
Parasitism in Didelphis sp. can express different physiological impacts resulting from the parasite load, as well as the affected organ. It is therefore pertinent to identify the sites and locations of infection to understand the possible effects on the host. The present work is a systematic literature review study on articles that described the presence of parasites and their respective sites of infection. Of the 114 studies retrieved in the literature, 54 were eligible to be included in this review. Based on the studies analyzed, the sites identified were organs and/or regions that include the: heart, mesenteric arteries, brain/cerebrum, oral mucosa, esophagus, stomach, small/large intestine, liver, gallbladder, lungs, bronchi, and bronchioles, in addition to other structures and regions. In terms of impact on the host, the analyzed infection sites suggest significant functional impairment, especially in digestive and respiratory structures. This may result in changes to behavioral, locomotion, reproductive capacity, and to losses in survival rates for the animals, in addition to modifying their interaction with the ecosystem and other species, including humans. The findings also reflect the ecological importance of opossums as intermediate and/or definitive hosts for a wide variety of helminths, many of which are of health concern due to their zoonotic potential.